Elevated progesterone level and its consequences on IVF - Das, Sankar Kumar; Roy, Priyanka; Kalita, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Understanding of the embryo-endometrium dialogue is still far from being understood. During conventional in vitro fertilization cycles, progesterone elevation on the day of human chorionic gonadotropin administration refers to rising progesterone levels in the absence of either premature or a luteinizing hormone surge. Most research have reported that elevated progesterone had an adverse impact on the endometrial environment of fresh cycles, leading to a decrease in pregnancy rates. Methods: The current study was undertaken at Swagat hospital and research Centre, Bongaigaon, Assam (India). Fifty patients undergoing in vitro fertilization (IVF) were selected for the study. Baseline estimation of follicle stimulating hormone (FSH), luteinizing hormone (LH), anti-Mullerian hormone (AMH), (estrogen) E2 and (transvaginal sonography) TVS was done. The patients were grouped on the basis of their progesterone levels on the day of hCG trigger, with the cutoff for defining premature progesterone rise being (progesterone) P4≥ 3ng/ml. Final oocyte maturation was induced with hCG. Oocyte retrieval was performed 34-36 h after hCG. Two to three embryos of day 3 cleavage stage were transferred under TVS guidance. The parameters obtained from each cycle were recorded. Statistical analysis was performed. Probability (P) value <0.05 was considered statistically significant. A sonographic confirmation of pregnancy was performed 2 weeks after β-hCG positive. Results: On dividing the patients into two groups, based on the cut off of P4 as 3ng/ml, it was observed that the no of cases that conceived was significantly higher in the subjects whose P4 level was less than or equal to 3ng/ml than the subjects whose P4 level was more than 3ng/ml. Conclusions: Elevated P4 i.e. Progesterone level just before trigger is a reflection of endometrial maturity that can cause disparity between endometrial and embryonic ageing and therefore hamper implantation or cause failure in assisted reproductive technology (ART).